Social Cognition, Self-Perceptions, and Social Withdrawal in Adolescents - Bosacki, Sandra Leanne; Talwar, Victoria; Sitnik, Valentina; Moreira, Flavia Pissoto; Coccimiglio, Maria; Quenneville, Shanel (Paedagogia Christiana, 2020)
This study explored individual differences in emotion recognition within the context of social orientations and self-perceptions. One hundred and forty-four Canadian adolescents (88 girls, 11–14 years), with a mean age of 13.4 years completed emotion recognition, perceived self-competencies, social preferences (shyness, unsociability, and regulated withdrawal), and social (dis)satisfaction measures. The highest scores were related to epistemic or neutral emotions, followed by negative and finally positive emotions. Furthermore, there were relationships between high levels of emotion recognition (negative emotions) and low levels of physical and global self-worth. Positive correlations were found between high levels of shyness and the ability to recognise negative and epistemic emotions, and experience feelings of low self-worth, with girls scoring higher than boys in recognising positive emotions. Adolescents characterised by high shyness and high social satisfaction (i.e., conflicted shyness) scored the highest on emotion recognition and feelings of low self-worth. Implications for the refinement of theory and research on social withdrawal and social cognition are discussed.